Global research trends and hotspots in calcaneal fracture: A bibliometric analysis (2000–2021) - Cai, Yang-Ting; Song, Yu-Ke; He, Min-Cong; He, Xiao-Ming; Wei, Qiu-Shi; He, Wei (Frontiers in Surgery, 2023)
Background Calcaneal fracture is common and carries high morbidity and disability. Its treatment is therefore of vital concern. Many topics concerning calcaneal fracture remain controversial, and the subject has not yet been well-researched. We aim to analyze and illustrate the trends in development, overall knowledge structure, “hotspots,” and research frontiers on the topic of calcaneal fracture. Methods Literature relating to calcaneal fracture published between 2000 and 2021 was retrieved from Science Citation Index Expanded (SCIE) database of the Web of Science. Three bibliometric tools (Bibliometrix, CiteSpace, and VOSviewer software) were used for analysis and the generation of knowledge maps. Annual trends in publication counts and the relative contributions of different countries, regions, institutions, authors, and journals, as well as keyword clusters, “hot topics,” and research frontiers, were analyzed. Results A total of 1,687 publications were included in the analysis. The number of calcaneal fracture articles published worldwide each year was highest in 2019, with a total of 128 articles. The United States has made the greatest contribution to the field, with the largest number of publications and the highest H-index. Foot & Ankle International was the most productive journal, publishing a total of 167 articles on calcaneal fracture during the study period. Hebei Medical University of China and the University of California, San Francisco were the most prolific institutions. Professors T. Schepers, S. Rammelt, H. Zwipp, and Y. Z. Zhang have made remarkable contributions to the field. However, the degree of collaboration between researchers and among institutions was relatively low, and took place mainly in Europe and the Americas. All relevant keywords could be categorized into three clusters: studies of internal fixation, studies of fractures, and studies of osteoporosis. A trend of balanced and diversified development could be seen within these clusters. Keywords with ongoing “citation bursts,” such as sinus tarsi approach, wound complications, minimally invasive technique, extensile lateral approach, surgical treatment, and plate, may continue to be research “hotspots” in the near future. Conclusion Based on current global trends, the number of publications on calcaneal fracture will continue to increase. Topics such as minimally invasive techniques and complications have become important hotspots of research. We recommend enhancing international communication and collaboration for future research in this field.